The Role of Technological Pedagogical Content Knowledge (TPACK) Instruction in Enhancing Creative Economic Thinking Abilities - Trianavera, Bernike Agnes; Pujiati, Amin; Santoso, Jarot Tri Bowo (Universitas Negeri Semarang, 2024)
Economics lessons are still perceived as boring due to the use of lecture-based teaching methods. This leads to a lack of students' ability to develop creative thinking potential and makes students tend to be passive. Therefore, an appropriate teaching method is required, namely the TPACK teaching method. The objective of this research is to determine the effectiveness of TPACK-based instruction in enhancing the creative thinking abilities of high school students in economics. This research is a quantitative research employing an experimental method with a nonequivalent control group design. The data collection techniques utilized in this research involve observation and testing methods. Based on the analysis results, the t-test calculations conducted using SPSS present an average score of 78.85 for the experimental group, which is higher when compared to the average score of 74.90 for the control group. This indicates that the enhancement of students' creative thinking abilities in economics using TPACK-based learning is more effective compared to the enhancement of students' creative thinking abilities using conventional learning.